2011
DOI: 10.1101/gad.176008.111
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially acting Sox transcription factors in neural lineage development

Abstract: Pluripotent embryonic stem (ES) cells can generate all cell types, but how cell lineages are initially specified and maintained during development remains largely unknown. Different classes of Sox transcription factors are expressed during neurogenesis and have been assigned important roles from early lineage specification to neuronal differentiation. Here we characterize the genome-wide binding for Sox2, Sox3, and Sox11, which have vital functions in ES cells, neural precursor cells (NPCs), and maturing neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
309
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(338 citation statements)
references
References 52 publications
22
309
0
1
Order By: Relevance
“…3A,B). SoxB1 transcription factors (Sox1, 2 and 3) play key roles in the active maintenance and fate determination of neural progenitors (Bergsland et al, 2011;Bylund et al, 2003;Graham et al, 2003;Oosterveen et al, 2012;Peterson et al, 2012). Examination of the Nkx2.2, Nkx6.1 and Olig2 datasets showed a consistent enrichment of a Sox motif in bound regions (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…3A,B). SoxB1 transcription factors (Sox1, 2 and 3) play key roles in the active maintenance and fate determination of neural progenitors (Bergsland et al, 2011;Bylund et al, 2003;Graham et al, 2003;Oosterveen et al, 2012;Peterson et al, 2012). Examination of the Nkx2.2, Nkx6.1 and Olig2 datasets showed a consistent enrichment of a Sox motif in bound regions (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…4A). Similarly, Sox3 DNA target interactions in neural progenitors (Bergsland et al, 2011) showed an extensive overlap with the repressor trio (46%) (supplementary material Fig. S6B).…”
Section: Resultsmentioning
confidence: 94%
“…Previous ChIP-seq studies have found that SOX2 is bound to hundreds of known or presumably poised loci that are transcriptionally inactive but will be expressed during differentiation (26,38); however, its biological role at these genes was unknown. It is widely accepted that bivalent domains are central to maintaining genes in a poised state, ensuring proper and robust responses to differentiation cues (57).…”
Section: Discussionmentioning
confidence: 99%
“…In NPCs, the chromatin regions of proneural and neurogenic genes contain high levels of both H3K27me3 and H3K4me3 (37,38); such bivalent marks maintain the genes transcriptionally silent but poised for activation once differentiation cues are received (32). To understand the regulatory function of SOX2 in activation of the neurogenic program, we examined previously published ChIP-sequencing (ChIP-seq) data including the occurrence of H3K27me3 and H3K4me3 marks at SOX2-binding sites in mouse ES cell-derived NPCs (6,26).…”
Section: Sox2 Deficiency Leads To Epigenetic Repression At the Promotersmentioning
confidence: 99%
“…26 Hypermethylated alive deserts were enriched for SOX gene family (P < 10 ¡51 ) and neurofibromin 1 (NF1) binding sites (P < 10 ¡22 ). SOX genes are involved in neuronal development 27 and axon regeneration 28 and NF1 has long been recognized for its critical role in the PNS.…”
Section: Alive and Dead Deserts Differ In Their Binding Site Motifmentioning
confidence: 99%